Prevalence, Risk Factors and Patterns of Different Underlying Enteropathogens in Pediatric Patients - Farman Ullah, Taj Muhammad, Rida Naz (Pakistan Journal of Medical & Health Sciences, 2023)
Background: According to the WHO, diarrhea is a result of inadequate water, sanitation, and hygiene and is the second leading cause of death in pediatrics. Objectives: Therefore, the study was intended to discover enteropathogens linked with diarrhea in pediatrics less than 5 years, their prevalence, distribution patterns and risk factors. Methods: The study was conducted in selected hospitals of District Dera Ismail Khan from March 2021 to October 2022 and comprised 384 patients diagnosed with bacterial (through culture) and parasitic (through microscopic examination) agents. Their demographic characteristics and risk factors were recorded on the pre-designed questionnaire. Results: Out of 384, 123 patients (32.03%) were suffering from bacterial diarrhea (p<0.05) and 261 children (67.96%) were diagnosed with parasitic ailments. Among bacterial causes, Escherichia coli (49.78%) was predominant (p<0.05), followed by Salmonella (18.92%), Campylobacter (10.66%), Shigella (7.13%) and Vibrio (1.91%), while the major parasitic infestation (p<0.05) involved Giardia (21.12%), Ascaris (17.78%), hookworms (14.39%), Trichuris (12.98%) Entamoeba (12.84%) and Taenia (3.19%). Most infected children belonged to the rural population (59.11%) than the urban (40.88%). Practical implications: The current study will pave a path for the clinicians to differentially diagnose the bacterial and parasitic origin enteropathogens in pediatric patients. Conclusion: Most of the diarrheic patients were diagnosed with parasitic than bacterial etiological agents. The major risk factors of the infection were poor hygiene, sanitation, weak immunity and playing of children in the contaminated soil and ingesting contaminated food materials. Keywords: Acute diarrhea; Parasites; Poor hygiene; Stool culture